Rendimento de milho com e sem adubação nitrogenada em função de épocas de dessecação da pastagem de azevém - Matos, Roberto Diego (2014)
The crop-livestock integration advises correlation of productive activities inside the rural property. In Brazil, corn is the most used cereal in the summer crops for crop rotation and reutilization of residual nutrients of the winter covers and pasture such as ryegrass, is usually intercropped with black oat. However, there is a consensus between technicians and farmers about a negative interference caused by ryegrassstraw in the corn cropbeing often assigned to allelopathy, nitrogen competition or plantability reduction. The study was conducted at a private property located in the county of Renascença – PR, from April 2013 to April 2014, with the aim to evaluate corn crop yield with and without nitrogen fertilization according to desiccation time of ryegrass pasture. A completely randomized block design arranged in split plots with four replications was used. The main plots were the desiccation time of ryegrass pasture (Lolium multiflorum Lam.) 30, 15 and 0 days before corn sowing (Zea mays L.) and the subplots were nitrogen levels 0 and 150 kg N ha-1. In the treatments with nitrogen was used urea (45% N) applied between the phenological stages V4 and V6. The variable evaluated on pasture was straw quantity and in the corn crop were evaluated main vegetative and yield components. Data were submitted to variance analysis and the interactions or the existence of significant effects of the treatments were evaluated by F test. Found statistical significance, the mean was compared using the Tukey test at 5% significance. Interaction between the factors desiccationtime of grazed ryegrass and nitrogen fertilization in corn for the variables stem diameter of corn plants and number of cobs per hectare occurred, being required an analysis of the best combination of these factors for each management situation. There was a significant difference for plant height and ear insertion height for the factor desiccation time, the lower plant and spikeheight was observed in the treatment of 0 days before sowing (DBS) that differed from the treatment of 15 (DBS) which did not differ from the 30 (DBS) treatment. There was no difference in yield in thedifferent factors that were evaluated, indicating that there is no need to anticipate desiccation ryegrass pasture that is properly managed. Regarding the final yield there was no difference in performing nitrogen fertilization, it can be anticipated by applying on the winter pasture.